Pengaruh Modul E-Jas Edutainment terhadap Karakter Peduli Lingkungan dan Tanggung Jawab - Savitri Wanabuliandari; Sekar Dwi Ardianti (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2018)
The purpose of this research was to: (1) find out the influence of E-JAS edutainment thematic module on environmental awareness character, and (2) find out the influence of E-JAS edutainment thematic module on the character of responsibility. The type of research used is quasi experiment, with the population of this research of fourth graders of SD Negeri in Kudus Regency. The research subjects were students of four grade in SD 2 Jati Kulon, District Jati, the Regency of Kudus in the academic year 2017/2018. The sampling technique was done by purposive sampling. The research design was one group pre-post test. The data collection techniques were non-test techniques through interviews and observation. Data analysis techniques which determine the effect of E-JAS edutainment module on environmental awareness character and responsibility used paired samples T-test. The result of this research was (1) there was an influence of E-JAS edutainment module towards environmental awareness character, and (2) there was an influence of E-JAS edutainment module towards the character of responsibility.